Idazoxan and the effect of intracerebroventricular oxytocin or vasopressin on sodium intake of sodium-depleted rats - Sato, M. A.; Sugawara, A. M.; Menani, José Vanderlei [UNESP]; DeLuca, L. A. (Elsevier B.V., 1997)
The alpha(2)-adrenergic agonist clonidine and the neuropeptide oxytocin, inhibit sodium intake when injected intracerebroventricularly (i.c.v.). The present work investigates whether (1) vasopressin also inhibits sodium intake when injected i.c.v., and (2) the effect of oxytocin and of vasopressin on sodium intake is affected by i.c.v. injection of idazoxan, an alpha(2)-adrenergic antagonist. Clonidine (30 nmol), oxytocin (40, 80 nmol) and vasopressin (40, 80 nmol) were injected i.c.v. 20 min prior to a 1.5% NaCl appetite test, in rats depleted of sodium for 24 h by a combination of a single s.c. injection of furosemide (10 mg/rat) and removal of ambient sodium. Every dose of clonidine, oxytocin and vasopressin inhibited the 1.5% NaCl intake. Seizures were observed with the higher dose of vasopressin, but not with either dose of oxytocin. The effect of i.c.v. injection of clonidine (30 nmol), oxytocin (80 nmol) or vasopressin (40 nmol) was partially inhibited by prior i.c.v. injection of idazoxan (160, 320 nmol). The results suggest that the inhibition of 1.5% NaCl intake induced by i.c.v. injection of neuropeptides in sodium-depleted rats depends, in part, on the activation of central alpha(2)-adrenoceptors. (C) 1997 Elsevier B.V. B.V. All rights reserved.
Keywords: clonidine; noradrenaline; salt intake; idazoxan; hypovolemia; dehydration